The scope of improvements in stainless steel and cast iron electrode market and the branding strategies of Linde Bangladesh Ltd: market analysis and suggestions - Rizwan Chowdhury, Rizwan Chowdhury (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.